Valuing Diversity : Buddhist Reflection on Realizing a More Equitable Global Future - Hershock, Peter D. (Book collections on Project MUSE., 2012)
This book uses Buddhist philosophy to discuss diversity as a value, one that can contribute to equity in a globalizing world. Diversity matters. Whether in the context of ecosystems, education, the workplace, or politics, diversity is now recognized as a fact and as something to be positively affirmed. But what is the value of diversity? What explains its increasing significance? This book is a response to these questions and to the contemporary global dynamics that make them so salient. The author examines the changes of the last century to show how the successes of Western-style modernity and industrially-powered markets have, ironically, coupled progressive integration and interdependence with the proliferation of political, economic, social, cultural, and environmental differences. Neither modern liberalism nor its postmodern critiques have offered the full resources needed to address such challenges. Making use of Buddhist and ecological insights, this book develops a conception of diversity as an emerging value and global relational commons, forwarding an ethics of interdependence and responsive virtuosity that opens prospects for a paradigm shift in our pursuits of equity, freedom, and democratic justice.